2016
DOI: 10.1016/j.jcmgh.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

A Disease-Associated Microbial and Metabolomics State in Relatives of Pediatric Inflammatory Bowel Disease Patients

Abstract: Background & AimsMicrobes may increase susceptibility to inflammatory bowel disease (IBD) by producing bioactive metabolites that affect immune activity and epithelial function. We undertook a family based study to identify microbial and metabolic features of IBD that may represent a predisease risk state when found in healthy first-degree relatives.MethodsTwenty-one families with pediatric IBD were recruited, comprising 26 Crohn’s disease patients in clinical remission, 10 ulcerative colitis patients in clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
156
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 51 publications
19
156
1
Order By: Relevance
“…Consistent with this, TAAR1 has been proposed to play a role in the susceptibility to fibromyalgia (Smith et al, 2012), TAAR6 implicated in treatment outcomes 598 in asthma (Chang et al, 2015), and TAAR2, TAAR5, and TAAR9 among the most highly upregulated genes in the inflamed zones of patients with Crohn disease (Taquet et al, 2012), an effect that allowed discrimination of these patients from those with irritable bowel syndrome. As previously indicated, two recent unbiased metabolomic studies have also identified elevated endogenous TAAR1 ligands in Crohn disease fecal samples (Jacobs et al, 2016;Santoru et al, 2017). Together, these studies indicate that a careful, systematic investigation of the ability of TAAR isoforms to regulate the immune system is warranted.…”
Section: Effects In the Peripherysupporting
confidence: 53%
See 1 more Smart Citation
“…Consistent with this, TAAR1 has been proposed to play a role in the susceptibility to fibromyalgia (Smith et al, 2012), TAAR6 implicated in treatment outcomes 598 in asthma (Chang et al, 2015), and TAAR2, TAAR5, and TAAR9 among the most highly upregulated genes in the inflamed zones of patients with Crohn disease (Taquet et al, 2012), an effect that allowed discrimination of these patients from those with irritable bowel syndrome. As previously indicated, two recent unbiased metabolomic studies have also identified elevated endogenous TAAR1 ligands in Crohn disease fecal samples (Jacobs et al, 2016;Santoru et al, 2017). Together, these studies indicate that a careful, systematic investigation of the ability of TAAR isoforms to regulate the immune system is warranted.…”
Section: Effects In the Peripherysupporting
confidence: 53%
“…Recent unbiased metabolomics studies indicated that elevated fecal PEA levels are present in patients with Crohn disease (Jacobs et al, 2016;Santoru et al, 2017), an effect that was suggested to contribute to the ability to discriminate these patients from healthy controls (Santoru et al, 2017). Similarly elevated TYR levels were reported in ulcerative colitis fecal samples (Santoru et al, 2017).…”
Section: Trace Amines and Their Receptorsmentioning
confidence: 95%
“…2 Similarly, feces from humans with inflammatory bowel disease contained more bile acids and taurine, and this metabolite pattern was highly correlated with a characteristic shift in the microbiota. 15 One study documented that the increased conjugated and sulfated bile acids in the feces of humans with Crohn's disease was attributed to the decreased capacity of the microbiome in these patients to deconjugate and desulfate bile acids, resulting in decreased production in the colon of secondary bile acids, which are normally anti-inflammatory. 16 Therefore, the increase in fecal taurine seen in human and animal models of inflammatory bowel disease likely results from a perturbation in microbiota, and consequently, bile acids may form the link between the dysbiosis and inflammation seen in these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In a new study published in this issue of Cellular and Molecular Gastroenterology and Hepatology , Jacobs et al 3 do exactly that. Performing a thorough analysis of fecal microbial profiles from 36 IBD patients in remission (26 with Crohn’s disease and 10 with ulcerative colitis) and 54 healthy first-degree relatives, they showed that it is possible to identify an IBD-like intestinal microbiome in at-risk healthy individuals who do not have clinically detectable inflammation.…”
mentioning
confidence: 85%
“…Going forward, prospective longitudinal studies in an expanded and more diverse cohort will be essential to determine whether the microbial signatures described by Jacobs et al 3 are indeed markers for a predisease state. Furthermore, because evidence suggests that mucosa-adherent microbes may correlate more tightly with the disease state than fecal communities, 5 it would be interesting to see whether typing using these communities could provide even more sensitive measures of susceptibility.…”
mentioning
confidence: 99%